Adsorptive removal of hexavalent chromium using sawdust: Enhancement of biosorption and bioreduction - Ng, Z.G. (Taylor and Francis Inc., 2017)
Simultaneous biosorption and bioreduction experienced by Cr(VI) species were initially validated by mixing 500 µM of Cr(VI) with 0.20 g of sawdust biosorbent. Accordingly, a complete disappearance of Cr(VI) species with emergence of 25 of Cr(III) ions was recorded; evidencing that both processes transpired simultaneously. An increase in the initial Cr(VI) concentration to 1500 µM could further induce more reduced Cr(VI) concentration. The enhancement of Cr(VI) biosorption and bioreduction was found to occur upon increasing the sawdust dosage to 4 g L−1 and decreasing the solution pH to 2. However, the presence of a Zn(II) co-pollutant at 2500 µM had deteriorated the removal of Cr(VI) species. © 2017 Taylor & Francis.